2023
DOI: 10.1021/acs.macromol.3c00356
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Local Dynamics in Mussel-Inspired Elastomers

Abstract: Materials with increased mechanical strength and toughness bearing mussel-inspired iron–catechol complexes and network architectures exhibit several dynamic features, e.g., high and broad glass-“transition” temperature, not explored so far. By combining differential scanning calorimetry and dielectric spectroscopy, the latter as a function of temperature and pressure, we have explored the increase in the glass temperature, T g, and the concomitant increase in the breath of T g in bioinspired networks bearing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Xia and co-workers have recently shown that increasing the strength of the cohesive interaction can lead to a significant increase in T g while at the same time leading to a significant decrease in the fragility of glass formation in the thermoset material. This competing effect has been observed recently in polymer network materials with cross-links intended to model charged physical cross-links found in mussels . These results collectively reveal another apparently general behavior of GF materials, changes in T g and fragility are related to factors altering the cohesive interaction strength of the material.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Xia and co-workers have recently shown that increasing the strength of the cohesive interaction can lead to a significant increase in T g while at the same time leading to a significant decrease in the fragility of glass formation in the thermoset material. This competing effect has been observed recently in polymer network materials with cross-links intended to model charged physical cross-links found in mussels . These results collectively reveal another apparently general behavior of GF materials, changes in T g and fragility are related to factors altering the cohesive interaction strength of the material.…”
Section: Introductionsupporting
confidence: 76%
“…This competing effect has been observed recently in polymer network materials with cross-links intended to model charged physical cross-links found in mussels. 38 These results collectively reveal another apparently general behavior of GF materials, changes in T g and fragility are related to factors altering the cohesive interaction strength of the material.…”
Section: Introductionmentioning
confidence: 62%
“…Experimental studies for systems in which the cohesive interaction strength increases through the introduction of charged and polymer groups have likewise indicated a tendency of T g to increase while fragility decreases as the molecular parameter influencing the cohesive interaction strength of the fluid increases. These systems include melts of polyzwitterion materials having increasing charge density, polymer networks with strong hydrogen bonding, weakly coordinating ionic physical cross-links, and ionomers of increasing charge density, where the decreased fragility is implied qualitatively by a significant broadening of the breadth of the glass transition. The variations of T g and fragility in the knotted ring and many-arm star polymer melts appear to follow this general pattern of behavior.…”
Section: Resultsmentioning
confidence: 99%